Insights on the structure of native CNF, an endogenous phospholipase A(2) inhibitor from Crotalus durissus terrificus, the South American rattlesnake - Fortes-Dias, Consuelo Latorre; Ortolani, Paula Ladeira; Fernandes, Carlos Alexandre H. [UNESP]; Lobo, Kelli Roberta; Melo, Lutiana Amaral de; Borges, Marcia Helena; Pazin, Wallance Moreira; Neto, Mario de Oliveira [UNESP]; Fernandez, Roberto Morato [UNESP]; Fontes, Marcos Roberto M. [UNESP] (Elsevier B.V., 2014)
Several snake species possess endogenous phospholipase A(2) inhibitors (sbPLIs) in their blood plasma, the primary role of which is protection against an eventual presence of toxic phospholipase A(2) (PLA(2)) from their venom glands in the circulation. These inhibitors have an oligomeric structure of, at least, three subunits and have been categorized into three classes (alpha, beta and gamma) based on their structural features. sb gamma PLIs have been further subdivided into two subclasses according to their hetero or homomeric nature, respectively. Despite the considerable number of sb gamma PLIs described, their structures and mechanisms of action are still not fully understood. In the present study, we focused on the native structure of CNF, a homomeric sb gamma PLI from Crotalus durissus terrificus, the South American rattlesnake. Based on the results of different biochemical and biophysical experiments, we concluded that, while the native inhibitor occurs as a mixture of oligomers, tetrameric arrangement appears to be the predominant quaternary structure. The inhibitory activity of CNF is most likely associated with this oligomeric conformation. In addition, we suggest that the CNF tetramer has a spherical shape and that tyrosinyl residues could play an important role in the oligomerization. The carbohydrate moiety, which is present in most sb gamma PLIs, is not essential for the inhibitory activity, oligomerization or complex formation of the CNF with the target PLA(2). A minor component, comprising no more than 16% of the sample, was identified in the CNF preparations. The amino-terminal sequence of that component is similar to the B subunits of the heteromeric sb gamma PLIs; however, the role played by such molecule in the functionality of the CNF, if any, remains to be determined. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phospholipase A(2) inhibitor; PLI; Phospholipase A(2); PLA(2); Crotalus; Quaternary structure